Teachers' Knowledge and Practice of Child Learning Assessment in Private and Public Pre- Schools. The Case of Shashemene City Administration, Oromia Region - Jima, Birhanu (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2021)
The purpose of this study was to assess teachers' knowledge and practice ofchild learning assessment in Shashemene city administration. In this study, a parallel convergent mixed research design was employed. A total of 10 private and 6 public pre-schools were involved in the study. In particular, a total of 117 samples, including 97 teachers, 16 school principals, and 4 cluster supervisors were recruited for data collection using questionnaires and interviews. In addition, focus group discussions, with a total of 24 participants were conducted among the key stakeholders of the pre-schools. Quantitative data were analyzed using descriptive statistics (percentage, frequency, mean and independent t-test). Qualitative data were analyzed using a narrative and thematic description. The result shows that teachers do nothave adequate knowledge and practice of child learning assessment and implementing different assessment techniques. The result also indicates that challenges such as a high ratio of children to teachers, lack of learning resources, and lack of proper supervision affect child learning assessment in the selected pre-schools. Therefore, better training for teachers, better management follow-up, parents' active participation in following up their children's results, equipping their children with proper knowledge, facilitating good and effective assessment practice in early childhood care and education need to be considered.